Applying Structural Equation Modeling for Accessing Mobile Banking Service Quality and Customer Satisfaction: A Case Study in Vietnam - Huy, Nguyen Quoc; Nga, Lu Phi; Tam, Phan Thanh (Journal of Applied Data Sciences, 2023)
Mobile Banking allows customers to use mobile devices and smartphones to conduct banking transactions anytime, anywhere. On the other hand, Mobile banking is a service product that brings high business efficiency, does not cost much, creates initiative for users, reduces pressure on over-the-counter transactions and has little risk, so developing developing mobile banking services brings great benefits to banks. Therefore, using scientific and technological achievements, particularly information technology, electronics, and telecommunications, has had a significant impact on daily life, the economy, and society, changing people's awareness and production and business methods in a wide range of fields and industries, including financial-banking services. In order to address the aforementioned analytical concerns, the authors performed a survey of 650 individual consumers who use mobile banking services at ten commercial banks in Vietnam. The authors employed structural equation modeling and data processing tools SPSS 20.0, Amos. Customer satisfaction is influenced by five elements, according to the findings: dependability, responsiveness, empathy, competence, and tangibles. The findings of the article had a significant reliability influence on individual customer satisfaction, with a significance level of sig 0.01. Finally, the study uniqueness validates ideas regarding customer satisfaction and service quality drivers, as well as the need of flexibly implementing customer satisfaction research policies.